What matters most? Understanding patient preferences in breast cancer treatment: A systematic review of discrete choice experiments - Chua, Pei Xuan; Soh, Song Hen; Ng, Qin Xiang; Zhou, Kevin Xiang; Chan, Joel Ming En; Yaow, Clyve Yu Leon; Goh, Serene Si Ning (The American journal of surgery, 2025)
Breast cancer treatment decisions often involve complex trade-offs between survival, quality of life, treatment burden, and financial costs. Understanding how patients weigh these factors is essential for patient-centered care. We conducted a systematic review following PRISMA guidelines, searching Medline, EMBASE, and the Cochrane Library databases up to February 28, 2025 for discrete choice experiment (DCE) studies involving adult women with breast cancer. Using a predefined protocol, two reviewers independently screened and extracted data and findings were narratively synthesized. Methodological quality was assessed using the ROBVALU tool. Seventeen studies (n ​= ​5873; 12 countries) were included. Treatment efficacy was the most important attribute in 88 ​% of studies. However, many patients, particularly younger women and those with early-stage disease, prioritized quality of life over modest survival gains. Notably, cost and logistical burden were influential in lower-income settings. Because many DCEs sampled advanced/metastatic populations, generalizability to low-risk early-stage disease is limited. In summary, patients often trade survival gains to reduce toxicity and treatment burden, underscoring the importance of integrating preferences into care decisions. •Synthesizes DCE evidence to clarify patient preferences in breast cancer treatment choices.•Patients often trade survival gains for lower burden, fewer side effects, and better quality of life.•Incorporating preferences into HTAs supports value-based care and more patient-centered decisions.